Examining the Mediating Role of Agile Supply Chain Approach between ERP System implementation and Organizational Performance - Munther Alnimer (International Journal of Supply Chain Management, 2019)
The study examine relationship between implementing ERP systems on the boosting of the organizational performance, in addition, to examine the mediating role of agile supply chain approach to achieve the targeted performance enhancements in manufacturing listed firms in Amman Stock Exchange (ASE). The study population entails all manufacturing listed firms in Amman Stock Exchange (ASE), particularly the top retail firms operate in the Jordanian market constitutes of (77) firms. The consent of conducting an interview has been taken with a total of (367) questionnaire were self-distributed. The unit of analysis is at a firm level, the deployed sample is a purposive sample. The study revealed that the ERP solutions are widely implemented in the mid and large sized organizations, due to its contribution in making all sub systems and modules communicate effectively, allowing the access to timely, and accurate information, under the set of authorization levels. Therefore, the Firm performance boosted as a result of implementing an effective ERP system. On the other side the study indicated that the implementing the agile supply chain approach as a method that would help in responding successfully to the customer and market demands, with no risk of having accumulated inventory on the stock. The study fulfils a novel aspect in examining the effect of ERP in the case of implementing the agility approach. The study encourages to consult expertise with the best practices to implement the ERP solutions in parallel with agile supply chain, also the yet to coming research need to focus of such factors rather than ERP effectiveness.